Adobe Photoshop Elements 2020 classroom in a book : the official training workbook from Adobe - Carlson, Jeff (Classroom in a book., 2020)
Adobe Photoshop Elements 2020 Classroom in a Book is the most thorough and comprehensive way for you to master Adobe's industry-leading consumer-targeted photo-editing software. Each chapter in this step-by-step, lesson-based guide contains a project that builds on your growing knowledge of the program, while end-of-chapter review questions reinforce each lesson. You will learn the basics of editing your images with Photoshop Elements and learn how to best use the program's many new features. This edition covers many new and improved features in Adobe Photoshop Elements 2020, including two tools based on Adobe Sensei AI technology that smooth skin to improve people's appearance while still looking natural, and colorize black and white photos or give a new look to color images. The revolutionary Select Subject feature makes complex selections in one click that would normally take much longer to create. And, of course, this edition includes Auto Creations delivered to your Home Screen and some of the latest guided edits, such as a fun way to paint patterns onto any photo. You'll discover new techniques that let you expand your creativity and improve your images from the other side of the photography process. And you'll learn how to print, export, and share your images.